2020
DOI: 10.1186/s13071-020-04285-x
|View full text |Cite
|
Sign up to set email alerts
|

Laboratory transmission potential of British mosquitoes for equine arboviruses

Abstract: Background: There has been no evidence of transmission of mosquito-borne arboviruses of equine or human health concern to date in the UK. However, in recent years there have been a number of outbreaks of viral diseases spread by vectors in Europe. These events, in conjunction with increasing rates of globalisation and climate change, have led to concern over the future risk of mosquito-borne viral disease outbreaks in northern Europe and have highlighted the importance of being prepared for potential disease o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
29
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 22 publications
(31 citation statements)
references
References 70 publications
1
29
1
Order By: Relevance
“…Consequently, investigating how repeated transmission in vectors may impact viral evolution and epidemiology with JEV warrants further investigation. Interestingly, Chapman et al 31 reported the recovery of JEV RNA from 72% of infected C. pipiens saliva samples at 18 °C, whereas we did not recover any JEV RNA in saliva at 20 °C. It is important to note that Chapman et al collected saliva at day 21 and the infection paradigm used JEV strain CNS138-11, which is representative of JEV genotype II 37 .…”
Section: Discussioncontrasting
confidence: 80%
See 3 more Smart Citations
“…Consequently, investigating how repeated transmission in vectors may impact viral evolution and epidemiology with JEV warrants further investigation. Interestingly, Chapman et al 31 reported the recovery of JEV RNA from 72% of infected C. pipiens saliva samples at 18 °C, whereas we did not recover any JEV RNA in saliva at 20 °C. It is important to note that Chapman et al collected saliva at day 21 and the infection paradigm used JEV strain CNS138-11, which is representative of JEV genotype II 37 .…”
Section: Discussioncontrasting
confidence: 80%
“…This corroborates experimental findings from other Cx. pipiens populations from the UK, Europe and Asia [29][30][31] . Given that we recorded such a marked increase in infection and dissemination prevalence at 25 °C it is likely that the limiting temperature at which Cx.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…pipiens to mice [ 90 ], and determine possible transmission by detecting JEV in the saliva of the mosquitoes as early as 7 dpi for a certain JEV isolate from China [ 94 ], and at 21 dpi in Cx . pipiens from the UK [ 95 ]. The virus was also found in the saliva of Cx .…”
Section: Resultsmentioning
confidence: 99%